The role of Leadership in improving HR Performance: in the Digital Age - Djoko Soelistya (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the role of leadership in improving human resource (HR) performance in the digital era. Digital transformation has altered work structures, communication patterns, and organizational expectations regarding employee performance, thereby requiring an adaptive and innovative leadership model. This research employs a quantitative approach using a survey method involving 120 respondents working in digital-based sectors. The research instrument was tested for validity and reliability and analyzed using multiple linear regression with the assistance of SPSS software. The results show that leadership has a positive and significant influence on HR performance, particularly in the dimensions of empowerment, inspiration, and digital adaptability. Conversely, an authoritative leadership style does not demonstrate a significant effect. These findings highlight the importance of developing technology-based and collaborative leadership to enhance organizational performance. The study recommends that organizations strengthen digital leadership training to cope with the increasingly complex dynamics of the workplace.